A RanBP2-type zinc finger protein functions in intron splicing in Arabidopsis mitochondria and is involved in the biogenesis of respiratory complex I - Bentolila, Stéphane (Nucleic Acids Res, 2021)
The RanBP2 zinc finger (Znf) domain is a prevalent domain that mediates protein interaction and RNA binding. In Arabidopsis, a clade of four RanBP2 Znf-containing proteins, named the Organelle Zinc (OZ) finger family, are known or predicted to be targeted to either the mitochondria or the plastids. Previously we reported that OZ1 is absolutely required for the editing of 14 sites in chloroplasts. We now have investigated the function of OZ2, whose null mutation is embryo lethal. We rescued the null mutant by expressing wild-type OZ2 under the control of the seed-specific ABSCISIC ACID-INSENSITIVE3 (ABI3) promoter. Rescued mutant plants exhibit severely delayed development and a distinctive morphological phenotype. Genetic and biochemical analyses demonstrated that OZ2 promotes the splicing of transcripts of several mitochondrial nad genes and rps3. The splicing defect of nad transcripts results in the destabilization of complex I, which in turn affects the respiratory ability of oz2 mutants, turning on the alternative respiratory pathway, and impacting the plant development. Protein-protein interaction assays demonstrated binding of OZ2 to several known mitochondrial splicing factors targeting the same splicing events. These findings extend the known functional repertoire of the RanBP2 zinc finger domain in nuclear splicing to include plant organelle splicing.